Self-Deception and Agential Authority . Constitutivist Account - Carla Bagnoli (Humana.Mente: Journal of Philosophical Studies, 2012)
This paper takes a constitutivist approach to self-deception, and argues that this phenomenon should be evaluated under several dimensions of rationality. The constitutivist approach has the merit of explaining the selective nature of self-deception as well as its being subject to moral sanction. Self-deception is a pragmatic strategy for maintaining the stability of the self, hence continuous with other rational activities of self-constitution. However, its success is limited, and it costs are high: it protects the agent’s self by undermining the authority she has on her mental life. To this extent, self-deception is akin to alienation and estrangement. Its morally disturbing feature is its self-serving partiality. The self-deceptive agent settles on standards of justification that are lower than any rational agent would adopt, and thus loses grip on her agency. To capture the moral dimension of self-deception, I defend a Kantian account of the constraints that bear on self-constitution, and argue that it warrants more discriminating standards of agential autonomy than other contemporary minimalist views of self-government.